Antibiotic Resistance: Moving From Individual Health Norms to Social Norms in One Health and Global Health - Hernando-Amado, Sara; Coque, Teresa M.; Baquero, Fernando; Martínez, José L. (Frontiers in Microbiology, 2020)
Antibiotic resistance is a problem for human health and, consequently, its study had been traditionally focused to its impact for the success of treating human infections in individual patients (Individual Health). Nevertheless, antibiotic resistant bacteria, and antibiotic resistance genes are not confined just to the infected patients. It is now generally accepted that the problem goes beyond humans, hospitals, or long-term facilities settings, and that it should be considered simultaneously in human-connected animals, farms, food, water, and natural ecosystems. In this regard, the health of humans, animals and local antibiotic-resistance-polluted environments should influence the health of the whole interconnected local ecosystem (One Health). In addition, antibiotic resistance is also a Global problem; any resistant microorganism (and its antibiotic resistance genes) could be distributed worldwide. Consequently, antibiotic resistance is a pandemic that requires Global Health solutions. Social norms, imposing individual and group behaviour that favour global human health and in accordance with the increasingly collective awareness of the lack of human alienation from Nature, will positively influence these solutions. In this regard, the problem of antibiotic resistance should be understood within the framework of socioeconomical and ecological efforts to ensure the sustainability of human development and the associated human-natural ecosystems interactions.